Lignocellulosic biomass conversion via greener pretreatment methods towards biorefinery applications. (February 2023) - Dharmaraja, Jeyaprakash; Shobana, Sutha; Arvindnarayan, Sundaram; Francis, Rusal Raj; Jeyakumar, Rajesh Banu; Saratale, Rijuta Ganesh; Ashokkumar, Veeramuthu; Bhatia, Shashi Kant; Kumar, Vinod; Kumar, Gopalakrishnan
Highlights: Structural composition of lignocellulose biomass was provided. Advanced green pretreatments on effective destruction of biomass have been discussed. Novel green solvent–based IL and DES pretreatment are discussed. Mechanistic path of greener ionic liquid pretreatment process has been deliberated. Supercritical carbon dioxide explosion ( Sc –CO2 ) has been documented. Abstract: Lignocellulose biomass during pretreatment releases various compounds, among them the most important is reducing sugars, which can be utilized for the production of biofuels and some other products. Thereby, innovative greener pretreatment techniques for lignocellulosic materials have been considered to open a new door in the aspects of digestibility of the rigid carbohydrate–lignin matrix to reduce the particle size and remove hemicellulose/lignin contents to successfully yield valid bioproducts. This article reviews about the composition of lignocelluloses and emphasizes various green pretreatments viz novel green solvent–based IL and DES steam explosion, supercritical carbon dioxide explosion (Sc–CO2) and co–solvent enhanced lignocellulosic fractionation (CELF) along with suitable mechanistic pathway of LCB pretreatment process. Finally, this article concludes that the existing pretreatments should be redesigned to conquer the demands by large scale production and suggests combined pretreatment methods to carry out various biomass pre–processing.